Water Poverty Assessment in Olorunsogo Local Government Area of Oyo State, Nigeria - P. I. Ifabiyi; B. Oladele; Wahab Salau (Department of Geography Education, University of Jember, 2020)
Poor access to water is often linked to poverty, human welfare, health, nutritional status, and household labour. This paper is aimed at contributing to the debate surrounding water poverty in the rural areas. Primary data obtained covering water resources, access, capacity, uses, and environment were collected using closed-ended questionnaires. Altogether, 370 household heads were sampled and were selected by systematic random sampling technique. Multiple correlations, factor analysis and multiple regression methods were used to determine the level of relationship between the Water Poverty Index (WPI) components. The results revealed that: WPI is the highest in Elenke/Sagbo (72.3%) and the lowest in Onigbeti II/Sagbon (55.5%). Also, WPI has a strong positive relationship with resources (r = .656), capacity (r = .705) and environment at 95%. Percentages of explanations of WPI ranges from 86.45% in Onigbeti I to 50.99% in Aboke.The results of multiple regression between WPI and components showed that components were weak predictors in 5 wards (Onigbeti III &IV, Onigbeti II , Onigbeti I, Seriki Agbele Aboke and Abogun wards). The paper posits that access to water in Olorunsogo Local Government Area (LGA) is generally reasonable. The paper suggests stronger government presence to improve and sustain the level of access. Keywords : Water Poverty; Access; Capacity; Uses; Environment; Resources; Factor Analysis Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License